Studi Pengaruh Stabilisasi Tanah Lempung Lunak Menggunakan Kolom Kapur Terhadap Parameter Kecepatan Penurunan Tanah - Arwan Apriyono; Sumiyanto Sumiyanto; Adhe Noor Patria SH (Jenderal Soedirman University, 2008)
Soft clay is kind of problem in building and highway foundation design. This type of soils, have low coefficient consolidation (Cv) parameter. This condition will cause that soils have very long duration in consolidation process. Limes column stabilization method can be applicable to solve this problem.This research be conducted to analyzed coefficient consolidation behavior in limes column stabilization method. The change variety of coefficient consolidation w ill be observe due to variation of limes column diameter. The limes column stabilization method be wished to increase the value of coefficient consolidation so settlement process of the soil get more rapidly. This research was conducted through experimentalin laboratory, with box that have 40 cm in diameters and this height is 40 cm. Five various of diameters applied in this research and this affect to value of Cv would be examined. Those are 3 cm, 5 cm, 8 cm, 10 cm and 12 cm diameters The result of this research show that limes column could increasing the value of coefficient consolidation. The average change of Cv is 0,000051 (6,38 %) compare w i th Cv without limes column stabilization. However, increasing of limes column diameters have no significant affects to the value of coefficient consolidation.